Improving Students’ Vocabulary Mastery Using Songs (Classroom Action Research at English Class B of Information Technology Program in Wira Wacana Christian University Sumba) - Riwa Rambu Hada Enda (Departement of Mathematics Education, 2023)
Pronunciation is focus on how to pronounce and produce the word. Students should be careful in pronouncing the word because in English there are some vocabulary that have almost similar pronunciation but different meaning. This research is Classroom Action Research (CAR). Classroom Action Research is a method of finding out what works best in your own classroom so that you can improve student learning. Method which was used in this research qualitative method research. Based on the diagram above, the students’ score in doing the test in cycle 2 can be seen that the percentage of students’ vocabulary mastery after songs were they got 49,44 for pronunciation, 71,84% for spelling, 37,04 for Grammar, 68,80% for Meaning. From the explanation, it could be concluded that only two of the vocabulary components that reach the target of minimum standard score: Spelling and Meaning. Teaching vocabulary using songs is one of the alternative solution, that teacher can use to teach vocabulary to their students. It makes students more relax in learning new words and they can memorize them easily.